Peran Jaksa dalam Mutual Legal Assistant dalam Pengembalian Korban Human Trafficking di Kamboja - Ramadhani, Setiawan; Nurrohman, Anisa Listiani; Nugroho, Hibnu; Rohmana, Nanda Yoga (Pusat Strategi Kebijakan Penegakan Hukum, Kejaksaan Agung, 2026)
The surge in online scam-based human trafficking cases in Cambodia affecting hundreds of Indonesian citizens calls for more efficient cross-border legal action. The urgency of this paper lies in analyzing the obstacles to coordination among prosecutors, such as differences in legal systems, complex bureaucracy, and limited access in foreign jurisdictions. Using a normative method with a case approach, this article evaluates the role of prosecutors in the Mutual Legal Assistance (MLA) mechanism to facilitate the repatriation and restitution of victims. The results show that the Attorney General's Office Bill strengthens the function of dominus litis and the executive authority of prosecutors in asset tracing and confiscation for victim compensation. In conclusion, strengthening the role of prosecutors as the central authority in MLA, supported by proactive legal diplomacy and digital technology, is crucial to overcoming structural barriers in Cambodia. This integration ensures that the restoration of victims' rights is carried out comprehensively in accordance with international standards.The surge in online scam-based human trafficking cases in Cambodia affecting hundreds of Indonesian citizens calls for more efficient cross-border legal action. The urgency of this paper lies in analyzing the obstacles to coordination among prosecutors, such as differences in legal systems, complex bureaucracy, and limited access in foreign jurisdictions. Using a normative method with a case approach, this article evaluates the role of prosecutors in the Mutual Legal Assistance (MLA) mechanism to facilitate the repatriation and restitution of victims. The results show that the Attorney General's Office Bill strengthens the function of dominus litis and the executive authority of prosecutors in asset tracing and confiscation for victim compensation. In conclusion, strengthening the role of prosecutors as the central authority in MLA, supported by proactive legal diplomacy and digital technology, is crucial to overcoming structural barriers in Cambodia. This integration ensures that the restoration of victims' rights is carried out comprehensively in accordance with international standards.